2010
DOI: 10.1016/j.fct.2009.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of high oral dose (−)-epigallocatechin-3-gallate in mice

Abstract: The tea polyphenol (-)-epigallocatechin-3-gallate (EGCG) has been studied for chronic disease preventive effects, and is marketed as part of many dietary supplements. However, case reports have associated the use of green tea-based supplements with liver toxicity. We studied the hepatotoxic effects of high dose EGCG in male CF-1 mice. A single dose of EGCG (1500 mg/kg, i.g.) increased plasma alanine aminotransferase (ALT) by 138-fold and reduced survival by 85%. Once-daily dosing with EGCG increased hepatotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
247
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(268 citation statements)
references
References 31 publications
13
247
2
6
Order By: Relevance
“…Recently, high-dose EGCG was reported to induce hepatotoxicity, as demonstrated by increased formation of malonyldialdehyde (MDA) and 4-hydroxynonenal (4-HNE) (Lambert et al 2010). Along a similar line, we found that EGCG enhanced the expression of pro-matrix metalloproteinase-7 by inducing oxidative stress in HT-29 human colorectal cancer cells (Kim et al 2007).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Recently, high-dose EGCG was reported to induce hepatotoxicity, as demonstrated by increased formation of malonyldialdehyde (MDA) and 4-hydroxynonenal (4-HNE) (Lambert et al 2010). Along a similar line, we found that EGCG enhanced the expression of pro-matrix metalloproteinase-7 by inducing oxidative stress in HT-29 human colorectal cancer cells (Kim et al 2007).…”
supporting
confidence: 70%
“…4a, b). Elevation of TBARS is a reliable indicator of lipid peroxidation, which might be closely related to tissue damage (Lambert et al 2010). As shown in Fig.…”
Section: General Observationsmentioning
confidence: 91%
“…Epigallocatechin gallate (EGCG) is the main active compound of non-fermented tea from Camellia sinensis, and several studies have shown the beneficial properties of tea made from its plant (BOSE et al, 2008;LAMBERT et al, 2009;MAKI et al, 2009;NOMURA et al, 2008;PHUNG et al, 2010;TAKAMI et al, 2008;ZHENG et al, 2004). In the present study, it was found approximately 20% of EGCG in the white tea extract, which may have an important role in the beneficial effects of tea found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we made sure that WTE was not hepatotoxic at the concentration used since Lambert (LAMBERT et al, 2009) reported the occurrence of liver damage when mice were supplemented with 1500 mg.kg -1 weight of green tea extract, which was characterized by increased serum alanine aminotransferase concentration and moderate necrosis. Takami (TAKAMI et al, 2008) estimated that the maximum daily dose of green tea that does not cause adverse effects in rats was around 750 mg.kg -1 body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of EGCG (450 mg) or green tea extract (1.2-4.5 g, corresponding to 100-300 mg EGCG) resulted in similar peak plasma concentrations in humans [106][107][108]. While EGCG has been recognized to be hepatotoxic in mice at concentrations of 500 mg/kg body weight and above and sporadic incidents of hepatotoxicity in humans have been reported [109,110], daily doses of 800 mg EGCG have been used in clinical trials without adverse effects (clinical trial NCT00951834) [111].…”
Section: Perspectives For Prevention and Therapymentioning
confidence: 99%